Effect of inflow conditions on the free-surface properties of hydraulic jumps. Issue 6 (2nd November 2021) - Felder, Stefan; Montano, Laura; Cui, Hanwen; Peirson, William; Kramer, Matthias
Abstract : Previous research has shown that the inflow conditions upstream of hydraulic jumps can affect flow aeration, bed pressures and turbulence. However, studies of the effects of inflow conditions on free-surface properties have not been conclusive and have lacked a comparison of partially and fully developed inflow conditions. Detailed measurements of the free-surface features in fully aerated hydraulic jumps with partially and fully developed inflow conditions have been conducted using a LIDAR. The results showed that the free-surface profile, the roller length, the free-surface and jump toe movements are strongly influenced by the inflow conditions. Hydraulic jumps with fully developed inflow conditions were of comparatively shorter length compared to partially developed hydraulic jumps, while they were characterized by stronger fluctuations, jump toe motions and frequencies as well as stronger energy loss across the hydraulic jump. Inflow conditions must be considered in determining the envelope of hydraulic jump motions with consequences for dissipator design.